2012
DOI: 10.1039/c2nr31409f
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nanostructured porous Cu–Au surfaces: the influence of cationic sites on (electro)-catalysis

Abstract: The fabrication of nanostructured bimetallic materials through electrochemical routes offers the ability to control the composition and shape of the final material that can then be effectively applied as (electro)-catalysts. In this work a clean and transitory hydrogen bubble templating method is employed to generate porous Cu-Au materials with a highly anisotropic nanostructured interior. Significantly, the co-electrodeposition of copper and gold promotes the formation of a mixed bimetallic oxide surface whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 94 publications
1
41
1
Order By: Relevance
“…The gold coverage estimated from EDX analysis for the 3 min of galvanic replacement gave a value of 9 wt %. This synergistic effect between Cu 2 O and Au, as well as the bimetallic Cu/Au system has been reported previously for heterogeneous catalysis reactions [ 33 , 46 , 47 , 68 , 69 ], as well as electrocatalytic reactions [ 33 , 70 , 71 , 72 ]. To ensure that the electrocatalytic response was not due to the reduction of residual oxides on the surface the same linear sweep voltammetry experiments were performed in the absence of nitrate ions ( Figure 6 c).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The gold coverage estimated from EDX analysis for the 3 min of galvanic replacement gave a value of 9 wt %. This synergistic effect between Cu 2 O and Au, as well as the bimetallic Cu/Au system has been reported previously for heterogeneous catalysis reactions [ 33 , 46 , 47 , 68 , 69 ], as well as electrocatalytic reactions [ 33 , 70 , 71 , 72 ]. To ensure that the electrocatalytic response was not due to the reduction of residual oxides on the surface the same linear sweep voltammetry experiments were performed in the absence of nitrate ions ( Figure 6 c).…”
Section: Resultssupporting
confidence: 81%
“…In electrocatalysis, bimetallic electrodes have been studied extensively, due to the synergy often seen when two metals are involved in a reaction [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Copper has also been alloyed with a variety of metals, such as Au, Ag, Pd and Pt to increase its (electro)-catalytic activity [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. A relatively simple way to make bimetallic electrodes is via galvanic replacement [ 36 , 37 , 38 , 39 , 40 ] where for example copper acts as the sacrificial metal, which oxidizes, and transfers electrons to a metal salt in solution, which is subsequently reduced at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Ag, Au and Pd nanomaterials have been investigated as catalysts towards this reaction, [18a, 19] and our previous work has shown that Cu/Au and Cu/Ag materials are also applicable for this reaction, which is beneficial as Cu is a much cheaper material than the more expensive noble metals. [12,20] Figure 6 displays kinetics data for the reduction of nitrophenol to aminophenol at Cu/Ag, Cu/Au and Cu/Pd. The reaction rates can be calculated by determining the slope of the linear part of the graph (assuming first-order kinetics given the excess concentration of NaBH 4 used).…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly useful given the critical role the aforementioned properties play in electrocatalysis, photocatalysis, surface enhanced Raman spectroscopy and electroanalytical chemistry. There are several approaches that can be undertaken to achieve a desired nanostructure such as using hard templates like anodised alumina [8,9], chemical templating with surfactants [10,11], inorganic ions [12,13], in situ underpotential deposition of a second metal [14], hydrogen bubbling [4,[15][16][17][18], or in the absence of any template via appropriate choice of metal precursor concentration and the applied potential/current waveform, time and temperature [19][20][21][22]. This illustrates the vast amount of parameters available for the creation of a wide range of interesting materials.…”
Section: Introductionmentioning
confidence: 99%